Kajian Proses Pengomposan Berbahan Baku Limbah Kotoran Sapi dan Kotoran Ayam - Putu Citra Dewi; Yohanes Setiyo; I Gusti Ngurah Apriadi Aviantara (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
The use of compost as an organic fertilizer is an effort to implement a Low External Input Sustainable Agriculture (LEISA) system. The application of this system can (1) improve land health, (2) increase soil fertility, and (3) improve soil physical properties. The main problem in some SIMANTRI programs is that the composting process does not produce good-quality compost that meets SNI (Indonesian National Standard), mainly due to the use of raw materials that do not meet the standard. This study aims to determine the best composition of cow manure and chicken manure to produce compost in accordance with compost quality standards. The experiment consisted of five treatments: KS = cow manure, KA = chicken manure, KSKA 2:1 = cow manure:chicken manure (2:1), KSKA 3:1 = cow manure:chicken manure (3:1), and KSKA 4:1 = cow manure:chicken manure (4:1). The analysis of compost quality was conducted in the Soil Science Laboratory, Faculty of Agriculture, Udayana University. The composting process was carried out for 2 months, with composting temperatures ranging from 22°C to 53°C and pH ranging from 4 to 7. The physical form of the compost resembled brownish-black soil. Generally, the quality of the compost produced fulfilled SNI 19-7030-2004 standards, with the best result obtained from KSKA 2:1 (cow manure:chicken manure = 2:1). The final results were temperature 27.04°C, pH 6.85, carbon 11.14%, nitrogen 0.64%, and a C/N ratio of 15.82%.